Analyzing the impact of conjunctive labeling as part of a regional wine branding strategy - Tom Atkin; Damien Wilson; Liz Thach; Janeen Olsen (Wine Economics and Policy)
Research studies have proven that place-based/regional branding methods have a positive effect on brand equity and economic benefits for companies. However, very small or specific regions may be confusing to consumers, so conjunctive labeling â or the process of advertising both a larger region and the sub-region of origin for a product â is suggested as a remedy for this situation. This study analyzes the impact of conjunctive labeling by comparing two national samples of consumers, before and two years after, conjunctive wine labeling was introduced in Sonoma County. The results show a higher awareness for both Sonoma County and its sub appellations (AVAs) after conjunctive labeling was introduced than before. This demonstrates the potential benefit of associating sub-regional appellations with larger wine regions. Keywords: Regional branding, Appellations, Wine marketing, Conjunctive labeling, Place-based marketing